The Intertwined Fates: Exploring the Triadic Relationship Between Internet Addiction, Psychological Capital, and Mental Health in Adolescents - Lalita (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The review investigates how internet addiction (IA) as well as psychological capital (PsyCap) and mental health (MH) relate to each other within the adolescent demographic. Modern society sees a rising trend in internet use among young people thus research on IA's relationship with MH requires understanding its mediation and moderation factors. This paper integrates research findings to document PsyCap components that include self-efficacy and optimism and hope and resilience in their associative and interactive roles with IA to affect adolescent MH. Research examines empirical data which demonstrates both straight and modified pathways between Internet Addiction and PsyCap toward Mental Health status while offering therapy approaches to handle the negative results of Internet Addiction while boosting optimistic psychological outcomes. The analysis demonstrates how research needs to focus on necessary future investigations by establishing research directions and detecting knowledge gaps for effective triangular variable integration.